Peranan Pendidikan Agama Islam Dalam Mengatasi Kenakalan Remaja Di SMP Pesantren Babakan Ciwaringin Kabupaten Cirebon - Absori, Absori; Rofiq, Muhammad Husnur; Zamawi, Bahrudin (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This research examines the role of Islamic religious education in overcoming juvenile delinquency at the Babakan Ciwaringin Islamic Boarding School Middle School, Cirebon. Using a qualitative case study type approach, this research collected data through observation, interviews, questionnaires and documentation studies. The results of the research revealed that there were cases of minor juvenile delinquency, such as skipping school, not doing assignments, and other violations of discipline. Causative factors include internal factors such as birth defects, negative traits, imbalance in meeting needs, and lack of positive hobbies, as well as external factors such as lack of parental attention, negative relationships, lack of means of channelling free time, and family/teacher ignorance in dealing with adolescent problems. Islamic religious education plays an important role in overcoming juvenile delinquency through instilling Islamic values in classroom learning and practices in the school environment, such as congregational prayers, religious lectures, maintaining cleanliness, shaking hands with teachers, and giving greetings, saying hello, smiling. This aims to form students' faithful, pious, and noble personalities to avoid deviant behaviour. This research contributes to the development of effective Islamic religious education strategies to overcome juvenile delinquency.